Spatial variability of soil and carbon sequestration in the Ganges moribund delta of Bangladesh: Spatial variability of soil and carbon sequestration (Dhaka University Journal of Biological Sciences, 2026)
This study investigates the spatial variability and controlling factors of soil organic carbon concentration (SOCC) and soil organic carbon density (SOCD) in the Moribund Delta, emphasizing their importance in carbon sequestration. A total of 25 soil samples were collected from five distinct land-use sites at varying soil depths. The distribution patterns of SOCC and SOCD showed substantial spatial variation, with the Sara sub-surface soils at the grassland site exhibiting the highest values—attributed to land-use differences—compared to other sites. Histogram analysis confirmed that soil organic carbon (SOC) stocks in the study area varied widely. Correlation analysis revealed positive relationships between SOCC and total nitrogen (TN), cation exchange capacity (CEC), soil bulk density, and clay content, highlighting their significance in carbon sequestration. Cluster analysis grouped soils into three distinct classes based on depth and organic carbon levels. Notably, Sara sub-surface soils acted as stronger SOC sinks, indicating the highest carbon sequestration potential. Principal Component Analysis (PCA) further demonstrated that SOCC is closely associated with fine-textured, nutrient-rich soils and negatively associated with sandy, nutrient-poor profiles. Overall, the findings underscore the vital role of deltaic soils in organic carbon storage and the need to improve soil fertility and organic matter management to maximize SOC sequestration—offering key strategies for climate change mitigation in vulnerable deltaic regions.Dhaka Univ. J. Biol. Sci. 35(1): 37-46, 2026 (January)